Utilization of viable bone marrow derivat stem cells through an adaption in low oxigen tension as an attempt to increase cellular transplantation efficacy for spermatogenesis process - Erma Safitri; Suzanita Utama; Candra Bumi; Sri Wigati Mardi; . Mulyani; . Helen; . Purwati; R. Heru Prasetyo; Mas’ud Hariadi; Fedik Abdul Rantam (Proceedings of The Annual International Conference, Syiah Kuala University - Life Sciences & Engineering Chapter, 2013)
Cellular transplantation using stem cells provides very promising solutions in the regeneration and repairment of cells that have experienced degeneration where recovery through medical or surgical intervension is impossible. However, the very low viability of transplanted stem cells limits the transplantation efficacy. The aim of this research was to obtain viable bone marrow derived stem cells by an adaptation treatment in a low oxygen tensioned in vitro culture. Low oxygen tension adaptation was adjusted to the niche of the stem cells in vivo. In this study, in vitro culture of stem cells in 1% oxygen was compared to those of the conventional culture in 21 % oxygen.Results showed that under 1% oxygentension cell proliferation was slower with larger or rounded triangle shaped cells, and senescence or dead cells was low. Meanwhile under 21 % oxygen tension cell proliferation was two fold faster with flattened and slender cells, and senescence or dead cells was higher. In conclusion, conventional in vitro culture under 21% oxygen caused cell aging (senescence) and rapid cell death, therefore the transplanted cells were not viable.